Measuring stick-style housing policies: A multi-country longitudinal database of governmental regulations - Konstantin A. Cholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper introduces a new international longitudinal database of governmental housing policies. The regulations are measured using binary variables based on a thorough analysis of the real-time country-specific legislation. Three major restrictive policies are considered: rent control, protection from restriction, and housing rationing. The database covers 47 countries and states between 1910 and 2018. This allows comparisons of regulation stringency across both time and space. The analysis reveals a surge of all restrictive policies in the first half of the 20th century. However, following World War II, the evolution of policies diverged: while rent control became more flexible or was phased out, tenure security stabilized at a high level or even increased, while housing rationing became used less frequently. An application of dynamic multivariate longitudinal clustering permits dividing the sample in two groups. One cluster comprises countries with more flexible rent control, stronger tenure security, and more housing rationing. It mostly includes European continental countries. Another cluster unifies countries with a more rigid rent control, weaker tenant protection, and rarely used housing rationing.
Keywords: C43; O18; R38; 330; regulation indices; rent control; tenure security; housing rationing